Ruse de Guerre Redux. Issue 3 (16th April 2021) - Verrall, Neil
Abstract : Deception has always been a valid stratagem of war. However, a number of important issues influence how deception could be used, or negated, within contemporary and future warfare. In this article, Neil Verrall clarifies the conceptual understanding of deception and recent developments within it, and highlights ongoing and new challenges. The article concludes by asking whether deception is still possible, or even desirable, in the 21 st century.◼